2017
DOI: 10.1111/apm.12747
|View full text |Cite
|
Sign up to set email alerts
|

Strong antimicrobial activity of xanthohumol and other derivatives from hops (Humulus lupulus L.) on gut anaerobic bacteria

Abstract: Strong antimicrobial activity of xanthohumol and other derivatives from hops (Humulus lupulus L.) on gut anaerobic bacteria. APMIS 2017; 125: 1033-1038.Anaerobic bacteria, such as Bacteroides fragilis or Clostridium perfringens, are part of indigenous human flora. However, Clostridium difficile represents also an important causative agent of nosocomial infectious antibiotic-associated diarrhoea. Treatment of C. difficile infection is problematic, making it imperative to search for new compounds with antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 20 publications
2
60
0
2
Order By: Relevance
“…Their effect on Bacillus , Streptomyces and Micrococcus strains was previously underlined [22,41]. Hops extracts are also able to combat some human pathogenic bacteria found in food, such as Clostridium perfringens and Listeria monocytogenes [42,43]. The screening conducted on some C. albicans strains showed that the spectrum of activity of hops extracts against these yeasts is weak, only two strains were susceptible to our extracts.…”
Section: Discussionmentioning
confidence: 79%
“…Their effect on Bacillus , Streptomyces and Micrococcus strains was previously underlined [22,41]. Hops extracts are also able to combat some human pathogenic bacteria found in food, such as Clostridium perfringens and Listeria monocytogenes [42,43]. The screening conducted on some C. albicans strains showed that the spectrum of activity of hops extracts against these yeasts is weak, only two strains were susceptible to our extracts.…”
Section: Discussionmentioning
confidence: 79%
“…According to phytochemical results, though both extracts of P. suberosa contain tannins, saponins and flavonoids, only the methanol extract showed antibacterial activities. The MIC values of conventional antibiotics are in the range of 15–107 µg/mL ( Cermak et al, 2017 ) and observed MIC values for methanol extract of P. suberosa ranged from 10–13 µg/mL indicating high antibacterial activity of the plant extract. Gram-negative bacteria pose a huge challenge in modern days due to emerging drug resistance of these pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, also the aqueous solubility at room temperature of 8-PN almost triples for an increase in pH from neutral to pH 8 (from 3 to 8 mg L −1 ) (Riis et al 2007). The theoretic dissociated fraction of the weak acids was approached using the Henderson-Hasselbalch equation for a range of pKa values for bitter acids, IX and 8-PN (Verzele and De Keukeleire 1991;Simpson and Smith 1992;Hermans-Lokkerbol et al 1997;Irwin and Shoichet 2005;Cattoor 2012; NCBI 2019; PhytoHub 2019a, 2019b; PubChem 2019) and indeed confirmed pH 7.8-8 could be the most optimal value for fermentation (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%